ANALISIS CRITICAL THINKING SKILL PADA MATERI PECAHAN DENGAN METODE INKUIRI MELALUI LESSON STUDY DI SD MAPANS - Alifia Melati Farida; Muhammad Zany; Indra Setiawati; Yuanata Ajeng Saputri; Eko Andy Purnomo; Venissa Dian Mawasari; Eny Winaryati (Litbang PWM Jawa Tengah, 2022)
The era of globalization and digitalization requires teachers to be able to innovate in managing learning. Proper management determines the success of learning. The success of learning is a series of stages of activities consisting of planning, implementation, and evaluation of learning. The quality of the learning planning stages will be better when they are compiled, implemented, and evaluated jointly by the learning team. Collaborative activities encourage participatory processes among members. Collaboration will develop and improve the learning process. Improving the quality of learning is a demand and obligation that must be done by the teacher. One way to improve the quality of learning is with lesson study activities. Critical thinking skills are very important because they can be used to solve problems and as considerations in making reasonable decisions about what to believe and what to do. A teacher needs to create a mathematics learning process that requires students to be able to develop their critical thinking skills. This study aims to analyze students' critical thinking skills in learning fractions using the inquiry method through lesson study activities for fourth grade students at SD Mapans (Muhammadiyah 08 Semarang) for the 2021/2022 academic year. The research method used is a qualitative approach with descriptive analysis methods. Recommendations that can be conveyed from this lesson study activity are (1) the ability of teachers to manage learning is very influential on the enthusiasm and response of students in participating in learning; (2) The varied learning media are able to attract students' interest and focus to participate in the learning process until the end of the activity; and (3) the right approach and method can improve the quality of learning. The conclusions from the implementation of this lesson study are (1) Learning through lesson study fosters critical thinking skills for both teachers and students; (2) Collaboration of various parties in preparing lesson plans through lesson study improves the ability of teachers to manage learning activities; and (3) the ability to think critically in students can be grown through an inquiry method approach which is collaborated in lesson study activities.